RECOGNISING NEW TRENDS IN VET TOWARDS GREEN TRANSITION: EXPERIENCE FROM NORTH MACEDONIA - Velkovska, Mila; Gecevska, Valentina; Polenakovikj, Radmil; Velkovski, Trajce; Jovanovski, Bojan; Polenakovikj, Liljana; Shterjova Uzunovska, Nastasija; Kostikj, Jelena (IATED, 2022)
Rapid technological, economic and social development requires inevitable changes and improvements, while sustainable development, environmental awareness and principles are increasingly becoming part of organisations' long-term strategies. The increasing benefits that come with implementing green approaches and concepts by connecting technology, innovation and sustainability are being more broadly recognised. The current global goal is to adapt existing and emerging technologies to satisfy both companies’ and customers’ needs, with minimal or no impact on the environment. Taking into account the continuous changes and the will for flexibility and timely reaction to them, there are needs to upgrade the existing knowledge and skills. Educational systems should be capable to react quickly to the changes and adjust their educational programmes in order to deliver a competent workforce. Greening of the existing occupations is highly recommended and vocational education and training (VET) have to be in line with industry needs and the demands of the labour market. In North Macedonia, vocational education and training are regarded as second-tier pathways to adulthood, designed for learners from less advantaged backgrounds. More than ever, employers from the industry are worried about the lack of well-trained and competent human resources who are willing to cope with today’s challenges and constant changes. In this paper, authors identify the trends in vocational education and training that enable or hinder the green transition in North Macedonia. For that purpose, a survey with more than 90 industry representatives, professors/teachers/educators and other stakeholders relevant for achieving green future, has been conducted in the period from January-August 2021. The survey analyses what is missing, what should be further developed and how to achieve the desired goals for improving vocational training in line with the green transition. Recommendations derived from the research will be submitted to the team responsible for development of a smart specialisation strategy (S3) in North Macedonia, as a potential response to the challenge of achieving structural changes for supporting knowledge-driven growth and technological, practice-based and social innovation. This research was conducted within the project “European VET Excellence Platform for Green Innovation”, co-funded by the Erasmus+ programme of the European Union (www.greenovet.eu).
Keywords: Green transition, green competences, vocational education and training.